Pengaruh Penggunaan Media Pembelajaran YouTube terhadap Keterampilan Menulis Puisi Peserta Didik Kelas VIII SMP Negeri 7 Kota Jambi - Zaldi, Fadli; Harahap, Eddy Pahar; Ningsih, Arum Gati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The aim of the research is to determine the influence of using YouTube learning media on the Poetry Writing skills of class VIII students at SMP Negeri 7 Jambi City. This research was carried out at SMP Negeri 7 Jambi City. This research took place from January 15 2024 to January 30 2024. The sampling technique used a purposive sampling technique from the population. Data collection techniques use tests and documentation. In this research, the tests that will be carried out are pretest and posttest. Data analysis techniques in this research are very important to determine learning outcomes in the learning process using YouTube learning media using test recapitulation. Before analyzing the data, things that need to be considered are carrying out pre-requisite tests for data analysis, including data normality tests, data homogeneity tests, and hypothesis tests. The research results show that the use of YouTube learning media in learning to write poetry has a significant influence in improving students' skills in writing poetry.Kata Kunci: Yotube, Menulis Puisi